LITERASI MATEMATIKA SISWA DALAM MEMECAHKAN MASALAH HOTS - Siti Wulandari; Christina Kartika Sari; Adi Nurcahyo; Rini Setyaningsih (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
Mathematical literacy is one of the needs of students to prepare themselves to be part of society in the future. Not only that, you are also required to be able to solve problems through higher order thinking skills (HOTS). The purpose of this research is to analyze students' mathematical literacy abilities in solving HOTS questions on circle material. This research is a qualitative descriptive study. The research subjects came from class VIII, which consisted of 32 students. Collecting data in this study was carried out through written tests and interviews. Checking the validity of the data using the triangulation technique compared the acquisition of interviews and tests. In conducting data analysis, it is divided into three components, namely data reduction, data presentation, and drawing conclusions. Based on the research results, all indicators of mathematical literacy have been achieved by students with high mathematical abilities. Meanwhile, students who have moderate mathematical abilities have achieved communication indicators, problem solving strategies, and representations. Finally, students who have low mathematical abilities have achieved indicators of problem solving and representation strategies. Therefore, the use of this research is to find out students' mathematical literacy abilities and to design better learning activities to increase students' mathematical literacy skills.